Euripides’ Hippolytos in Aristophanes: Eὐριπιδαριστοφανίζειν through Ἱππολυτίζειν - Zagari, Effie (Pnyx: Journal of Classical Studies, 2024)
Aristophanes’ paratragic and parodic relationship with Euripides has long been discussed in classical scholarship mainly due to the numerous references to Euripides and his tragedies in Aristophanes’ comedies. This article focuses on the use and re-use of the myth of Hippolytos in Aristophanes, as it is found in Euripides’ extant play. The references to Hippolytos found in Aristophanes’ extant and fragmentary plays will be discussed. One of the main purposes of this paper is to bring into attention not only the references to Euripides’ Hippolytus in the extant plays but also in the fragments, which have been rather interesting in terms of their scale and nature as they are very different to the ones found in the extant plays, where the focus of the parody is mainly the character of Phaidra. Aristophanes is donning Euripides’ costumes to serve his purposes and scenarios. The present essay navigates through how Aristophanes used the same Euripidean disguise not just to εὐριπιδαριστοφανίζειν but specifically to ἱππολυτίζειν within his oeuvre.